Developmental trajectories of body mass index from childhood into late adolescence and subsequent late adolescence–young adulthood cardiometabolic risk markers - Oluwagbemigun, Kolade; Buyken, Anette; Alexy, Ute; Schmid, Matthias; Herder, Christian; Nöthlings, Ute (Cardiovascular Diabetology)

Chancen des digitalen Lernens in der Ganztagsschule - Eickelmann, Birgit; Drossel, Kerstin (Jahrbuch Ganztagsschule 2019/20)

Potenziale der Tabletnutzung im Unterricht zur individuellen Förderung – Analysen und Forschungsperspektiven - Drossel, Kerstin; Eickelmann, Birgit (Individuelle Förderung im Unterricht. Empirische Befunde und Hinweise für die Praxis)

Die Implementation digitaler Medien gestalten: zur Bedeutung der Einstellungen von Fremdsprachenlehrkräften - Drossel, Kerstin; Eickelmann, Birgit (Lehrer. Bildung. Gestalten. Beiträge zur empirischen Forschung in der Lehrerbildung)

Soziale Herkunft und computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich - Senkbeil, Martin; Drossel, Kerstin; Eickelmann, Birgit; Vennemann, Mario (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Nutzung digitaler Medien und Prädiktoren aus der Perspektive der Lehrerinnen und Lehrer im internationalen Vergleich - Drossel, Kerstin; Eickelmann, Birgit; Schaumburg, Heike; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Digitalisierung im deutschen Bildungssystem im Kontext des Schulreformdiskurses - Eickelmann, Birgit; Drossel, Kerstin (Schulreform – Zugänge, Gegenstände, Trends)

Berufliche, pädagogische und didaktische Professionalisierungsmaßnahmen in der Sekundarstufe im Zeitalter der Digitalisierung und der Zusammenhang mit der Förderung digitaler Kompetenzen von Schülerinnen und Schülern - Drossel, Kerstin; Eickelmann, Birgit; Port, Sonja; Lorenz, Ramona (Transfer zwischen Lehrer(fort)bildung und Wissenschaft)

Digitalisierung und Bildungsgerechtigkeit – die schulische Perspektive - Drossel, Kerstin; Eickelmann, Birgit; Vennemann, Mario (DDS – Die Deutsche Schule)

Was bedeutet die Digitalisierung für die Lehrerfortbildung? – Ausgangslage und Perspektiven - Eickelmann, Birgit; Drossel, Kerstin; Port, Sonja (Nachhaltige Professionalisierung für Lehrerinnen und Lehrer: Ideen, Entwicklungen, Konzepte)

Price competition and the Bertrand model: The paradox of the German mobile discount market - Kaimann, Daniel; Hoyer, Britta (Applied Economics Letters)
We investigate the degree of price competition among telecommunication firms. Underlying a Bertrand model of price competition, we empirically model pricing behaviour in an oligopoly. We analyse panel data of individual pricing information of mobile phone contracts offered between 2011 and 2017. We provide empirical evidence that price differences as well as reputational effects serve as a signal to buyers and significantly affect market demand. Additionally, we find that brands lead to an increase in demand and thus are able to generate spillover effects even after price increase.

Is It Worth the Attention? A Comparative Evaluation of Attention Layers for Argument Unit Segmentation - Spliethöver, Maximilian; Klaff, Jonas; Heuer, Hendrik (Proceedings of the 6th Workshop on Argument Mining)
Attention mechanisms have seen some success for natural language processing downstream tasks in recent years and generated new state-of-the-art results. A thorough evaluation of the attention mechanism for the task of Argumentation Mining is missing. With this paper, we report a comparative evaluation of attention layers in combination with a bidirectional long short-term memory network, which is the current state-of-the-art approach for the unit segmentation task. We also compare sentence-level contextualized word embeddings to pre-generated ones. Our findings suggest that for this task, the additional attention layer does not improve the performance. In most cases, contextualized embeddings do also not show an improvement on the score achieved by pre-defined embeddings.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Schlussbericht zum Vorhaben "Additive Leichtbaustrukturen für Flugzeugkomponenten" : Verbund: KOBFS - Kostenoptimierter Baukasten für Flügelsysteme - Ahlers, Dominik; Tröster, Thomas

The Other Side of the Same Coin – How Communal Beliefs About Entrepreneurship Influence Attitudes Toward Entrepreneurship - Jakob, Eva Alexandra; Isidor, Rodrigo; Holger, Steinmetz; Marius, Wehner; Kabst, Rüdiger (Journal of Vocational Behavior)

The Contextual Role of Regulatory Stakeholder Pressure in Proactive Environmental Strategies: An Empirical Test of Competing Theoretical Perspectives - Jakob, Eva Alexandra; Baum, Matthias; Huett, Pascal; Kabst, Rüdiger (Organization & Environment)

Nationale Forschungsdateninfrastruktur, die Initiative NFDI4Culture und die Musikwissenschaft - Pasdzierny, Matthias; Röwenstrunk, Daniel; Schmidt, Dörte (Die Musikforschung)

Fokusthemen und Aufgabenbereiche für eine Forschungsdateninfrastruktur zu materiellen und immateriellen Kulturgütern. Living Document der NFDI-Initiative NFDI4Culture. - Altenhöner, Reinhard; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Blümel, Ina; Bulle, Klaus; Effinger, Maria; Hammes, Andrea; Hartmann, Thomas; Kailus, Angela; Kett, Jürgen; Pittroff, Sarah; et al.

Virtual reality interventions for balance prevention and rehabilitation after musculoskeletal lower limb impairments in young up to middle-aged adults: A comprehensive review on used technology, balance outcome measures and observed effects - Vogt, Sarah; Skjæret-Maroni, Nina; Neuhaus, Dorothee; Baumeister, Jochen (International Journal of Medical Informatics)

Who Sets the Tone? Determining the Impact of Convergence Behaviour Archetypes in Social Media Crisis Communication - Mirbabaie, Milad; Bunker, D.; Stieglitz, S. (Information Systems Frontiers)